1997
DOI: 10.1523/jneurosci.17-10-03804.1997
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Control of Location-Specific Information in Tactile Cutaneous Reflexes from the Foot during Human Walking

Abstract: The purpose of the present study was to determine whether tactile cutaneous reflexes from the skin of the foot contain location-specific information during human walking. Muscular responses to non-nociceptive electrical stimulation of the sural, posterior tibial, and superficial peroneal nerves, each supplying a different skin area of the foot, were studied in both legs during walking on a treadmill. For all three nerves the major responses in all muscles were observed at a similar latency of ϳ80-85 msec. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
149
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(171 citation statements)
references
References 45 publications
20
149
2
Order By: Relevance
“…This loss in training ability is correlated to a reorganization of the plantar flexors activation patterns that is also attributed to the removal of plantar cutaneous input (Bouyer and Rossignol, 2003a,b). Similar effects have been reported for people with a sensory polyneuropathy of the feet, where a large variability in the step cycle duration and associated gait impairment are associated with a loss of reflex action of low-threshold cutaneous afferents (Van Wezel et al, 1997). In this respect, when foot sole stimulation is used as a conditioning stimulus it can depress soleus H-reflex excitability during assisted walking of people with a chronic SCI, resulting in a more normalized soleus H-reflex modulation pattern during walking (Fung and Barbeau, 1994).…”
Section: Introductionsupporting
confidence: 77%
“…This loss in training ability is correlated to a reorganization of the plantar flexors activation patterns that is also attributed to the removal of plantar cutaneous input (Bouyer and Rossignol, 2003a,b). Similar effects have been reported for people with a sensory polyneuropathy of the feet, where a large variability in the step cycle duration and associated gait impairment are associated with a loss of reflex action of low-threshold cutaneous afferents (Van Wezel et al, 1997). In this respect, when foot sole stimulation is used as a conditioning stimulus it can depress soleus H-reflex excitability during assisted walking of people with a chronic SCI, resulting in a more normalized soleus H-reflex modulation pattern during walking (Fung and Barbeau, 1994).…”
Section: Introductionsupporting
confidence: 77%
“…Nevertheless, the pilot results are not trivial and may be of interest since they shed some light on the effect of foot pressure and central processing. For instance, from various cutaneous reflexes (Aniss et al, 1992;van Wezel et al, 1997;Yang & Stein, 1990;Zehr & Stein, 1999) one might expect to see a direct effect of foot pressure on motor patterns. In addition, it is well known that loss of cutaneous sensation from the foot can compromise stability in locomotion (Courtemanche et al, 1996;Dingwell & Cavanagh, 2001;Perry et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the organization of the interneuronal network for locomotion and the use of corrective reactions during walking points toward a rule-based finite control system rather than a simple additive principle of multisensory fusion (Misiaszek, 2006;Prochazka, 1996). A number of cutaneous reflexes may also participate in the fine control of foot positioning in animals (Guertin, Angel, Perreault, & McCrea, 1995;Schouenborg & Weng, 1994) and humans (Abbruzzese, Rubino, & Schieppati, 1996;Aniss, Gandevia, & Burke, 1992;Sayenko et al, 2007;van Wezel, Ottenhoff, & Duysens, 1997;Yang & Stein, 1990;Zehr & Stein, 1999). Nevertheless, the functional role of specific groups of sensory receptors in regulating human locomotion is still uncertain because they cannot be easily separated since they interact with each other and with central rhythm-generating centers in a complex manner.…”
Section: Introductionmentioning
confidence: 99%
“…3,11,26,54 Furthermore, CR is actively modulated during passive movement, 55 balance 56 and gait. 26,39,56 As such, it is surprising that only one study has observed abnormal CR activity in subjects with the spasticity syndrome during gait after incomplete SCI. 11 Higher Pl-TA CR activity in subjects diagnosed specifically with the SCI spasticity syndrome, detected without a change in background TA EMG activity during controlled ramp and hold phases of plantarflexion, supports further characterisation of cutaneous hyperreflexia as a test of spasticity for this pathology.…”
Section: Discussionmentioning
confidence: 99%
“…11,38,39 First, background EMG signal activity was subtracted from evoked TA reflex activity. Second, reflex activity ratios were calculated between the ramp or hold phases of plantarflexion and activity measured during the rest period.…”
Section: Cr Measurement and Analysismentioning
confidence: 99%